Antifungal Activities of Neobalanocarpus heimii (Cengal) Heartwood Extracts on Trametes versicolor and Coniophora puteana - Nur Afiqah Manan; Ismail Jusoh; Furzani Pa'ee (Journal of Tropical Biodiversity and Biotechnology, 2022)
Neobalanocarpus heimii (Cengal) is from the family Dipterocarpaceae. It is a long-lasting wood that is also one of the most robust timbers in the world. This species is native to Peninsular Malaysia and southern Thailand. In this study, the Cengal heartwood was studied concerning the amount of water extractive content with antifungal properties from the Neobalanocarpus heimii. The dilution method was used to test the antifungal properties. Wood meals samples were subjected to the sequential extractive beginning with hexane followed by dichloromethane, methanol and water. The extracts were collected and underwent evaporation by using rotary evaporator to obtain pure crude extract. The antifungal activities were determined using agar dilution method. Two selected fungi Trametes versicolor (T. versicolor) and Coniophora puteana (C. puteana) were used. The antifungal index (%) which compares the diameter of the growth zone for the experimental plate and control plate was calculated. The total percentage of yield from Neobalanocarpus heimii was 0.28%. The highest antifungal index obtained for Trametes versicolor (T. versicolor) was 81.22%, while C. puteana was 43.24%. The crude extracts from Neobalanocarpus heimii were effective in inhibiting the growth of Trametes versicolor and Coniophora puteana.